The Growth of Anglonema Dus Anjamani Plants Due to the Composition of the Growing Medium and Different Water Intervals - Sine, Heny M.C.; Sudarma, I Komang; Lende, Aloysius Ngongo (Ridwan Institute, 2024)
This research investigates the influence of planting media and watering intervals on the growth of Aglaonema. The study utilizes a Randomized Group Design (RAK) with various compositions of planting media, including husk charcoal, chicken manure bokashi, and eggshell flour, in ratios M1=1:2:1, M2=2:1:2, M3=3:2:1. Watering time intervals were set as I1=once every 2 days, I2=once every 4 days, and I3=every 6 days. There were 27 experimental units, each combination repeated thrice. Statistical analysis, including Sidik Ragam and Duncan's New Multiple Range Test (DNMRT), revealed a significant interaction effect between planting media and watering intervals on plant height, leaf number, leaf length, and leaf width of Aglaonema. Notably, the composition 3:2:1 showed the highest growth in plant height (5.03cm), leaf number (4.53 strands), leaf length (4.83cm), and leaf width (4.13cm). This composition did not significantly differ from 1:2:2 with a 2-day watering interval and 3:2:1 with a 2 and 6-day watering interval, but it significantly outperformed other treatments. The findings contribute valuable insights into optimizing Aglaonema growth conditions for enhanced quality and productivity.